Monstrous beings and media cultures : folk monsters, im/materiality, regionality - Balanzategui, Jessica; Craven, Allison (Amsterdam : Amsterdam University Press, 2023)
Monstrous Beings of Media Cultures examines the monsters and sinister creatures that spawn from folk horror, Gothic fiction, and from various sectors of media cultures. The collection illuminates how folk monsters form across different art and media traditions, and interrogates the 21C revitalization of "folk" as both a cultural formation and aesthetic mode. The essays explore how combinations of vernacular and institutional creative processes shape the folkloric and/or folkoresque attributes of monstrous beings, their popularity, and the contexts in which they are received. While it focuses on 21C permutations of folk monstrosity, the collection is transhistorical in approach, featuring chapters that focus on contemporary folk monsters, historical antecedents, and the pre-C21st art and media traditions that shaped enduring monstrous beings. The collection also illuminates how folk monsters and folk "horror" travel across cultures, media, and time periods, and how iconic monsters are tethered to yet repeatedly become unanchored from material and regional contexts.
Introduction -- Folk Monsters and Monstrous Media: The Im/materialities, Modalities, and Regionalities of Being(s) Monstrous (Allison Craven and Jessica Balanzategui) Chapter One -- The Momo Challenge as Urban Legend: Child and Adult Digital Cultures and the Global Mediated Unconscious (Jessica Balanzategui) Chapter Two -- Every Imaginable Invention of the Devil: Summoning the Monstrous in Eurocentric Conceptions of Voodoo (Karen Horsley) Chapter Three -- The Forest and the Trees: The Woods as Intersection between Documentary, Fairy Tale, and Internet Legend in Beware the Slenderman (Naja Later) Chapter Four -- Mark Duplass as Mumbelgore Serial Killer: Fictional Vernacular Filmmaking in the Creep series (Andrew Lynch) Chapter Five -- Monsters in the Forest: 'Little Red Riding Hood' Crimes and Ecologies of the Real and Fantastic (Cristina Bacchilega and Pauline Greenhill) Chapter Six -- A Mother's Milk: Motherhood, Trauma, and Monstrous Children in Folk Horror (Emma Maguire) Chapter Seven -- Documenting the Unheard: The Poetics of Listening and Empathy in The Family (Stephen Gaunson) Chapter Eight -- Reimagining the Pontianak Myth in Malaysian Folk Horror: Flexible Tradition, Cinema, and Cultural Memory (Andrew Ng) Chapter Nine -- An Uncommon Ancestor: Monstrous Emanations and Australian Tales of the Bunyip (Allison Craven) Chapter Ten -- The Folk Horror "Feeling": Monstrous Modalities and the Critical Occult (Jessica Balanzategui and Allison Craven)
"Amsterdam University Press"
Description based on online resource; title from digital title page (viewed on September 18, 2023).
JSTOR
Keywords: Monsters -- Folklore; Monsters in mass media; Monsters in popular culture; Monstres -- Folklore; Monstres dans les médias.; Monstres dans la culture populaire; Film: styles and genres; Classic horror and ghost stories; PERFORMING ARTS / Film / Genres / Horror; SOCIAL SCIENCE / Folklore & Mythology; Monsters; Monsters in mass media; Monsters in popular culture; Horror and supernatural fiction; Folklore, myths and legends; Mythical and legendary beings, monsters and creatures; Film, Media, and Communication; FMC; Cultural Studies; CULTURAL; Interdisciplinary Studies; INTERDISC; Media Studies; MEDIA; Psychology; PSYCH; Monsters, folk, immateriality, regionality, folkloresque, Gothic; Folklore